A heat-resistant low-expansion glass container and a method for manufacturing the same

CN122916397APending Publication Date: 2026-10-16祁县力多玻璃制品有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611211054.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]针对现有技术的不足,本发明提供了一种耐热低膨胀玻璃容器及其制备方法,解决现有耐热玻璃容器制备过程中硼源容易挥发,导致成型玻璃液中三氧化二硼的实际含量偏离设计含量的问题

Benefits of technology

[0021] 1. This invention divides the boron source into a first boron source and a second boron source. The second boron source, all lithium sources, 50% to 80% of the total potassium source, 20% to 40% of the total aluminum source, and 5% to 12% of the total silicon source are pre-reacted without the addition of a sodium source. After the formation of the base glass melt, a boron-containing pre-reactant is added. This reduces the volatilization of the boron source during the high-temperature melting process, improves the retention rate of boron trioxide content, and makes the actual boron trioxide content close to the design content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916397A_ABST
    Figure CN122916397A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of glass container preparation, and discloses a heat-resistant low-expansion glass container and a preparation method thereof. A boron source is divided into a first boron source and a second boron source, 50-80% of the total amount of a potassium source, 20-40% of the total amount of an aluminum source, and 5-12% of the total amount of a silicon source are pre-reacted under the condition of not adding a sodium source to obtain boron-containing pre-reacted material with a water-soluble boron ratio of 8-18%; the first boron source, all sodium sources, the remaining potassium source, the remaining aluminum source, the remaining silicon source, and all magnesium sources, all calcium sources, and all zirconium sources are made into a base batch and are smelted to obtain base glass liquid, the boron-containing pre-reacted material is added into the base glass liquid in 2-4 times, and the heat-resistant low-expansion glass container is obtained through smelting, shaping, and annealing. The present application can improve the retention rate of boron trioxide content, and improve the uniformity of thermal expansion performance and heat shock resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of glass container manufacturing technology, specifically to a heat-resistant, low-expansion glass container and its manufacturing method. Background Technology

[0002] Heat-resistant glass containers are typically made of borosilicate glass. By introducing boron trioxide into the glass composition, the thermal expansion of the glass is reduced, and the container's ability to withstand temperature changes is improved. Existing borosilicate glass is usually produced by mixing silicon, boron, aluminum, sodium, and other raw materials and then melting them at high temperatures. Some manufacturers also employ methods such as batch pretreatment, staged heating, or pre-melting of boron-containing raw materials to improve raw material melting and glass homogenization.

[0003] However, in the existing process of preparing heat-resistant glass containers, the boron source is prone to volatilization during high-temperature melting, causing the actual content of boron trioxide in the molten glass to deviate from the designed content, which in turn affects the compositional stability of the heat-resistant low-expansion glass container. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a heat-resistant, low-expansion glass container and its preparation method, solving the problem that the boron source is prone to volatilization during the preparation of existing heat-resistant glass containers, causing the actual boron trioxide content in the molten glass to deviate from the designed content.

[0005] To achieve the above objectives, the present invention provides a method for preparing a heat-resistant, low-expansion glass container, comprising the following steps:

[0006] S1. According to the designed mass of boron trioxide in the molten glass, the boron source is divided into a first boron source and a second boron source. The boron trioxide mass corresponding to the first boron source accounts for 30% to 50% of the designed boron trioxide mass, and the boron trioxide mass corresponding to the second boron source accounts for 50% to 70% of the designed boron trioxide mass. The sum of the boron trioxide mass corresponding to the first boron source and the boron trioxide mass corresponding to the second boron source is the designed boron trioxide mass.

[0007] S2. Mix the second boron source, all lithium sources, 50% to 80% of the total amount of potassium source, 20% to 40% of the total amount of aluminum source, and 5% to 12% of the total amount of silicon source, and carry out a pre-reaction without adding sodium source to obtain a boron-containing pre-reaction material with a water-soluble boron ratio of 8% to 18%.

[0008] S3. Mix the first boron source, all sodium source, the remaining potassium source, the remaining aluminum source, the remaining silicon source, all magnesium source, all calcium source, and all zirconium source to obtain a basic batching material. Melt the basic batching material at 1380℃~1450℃ for 30min~90min to obtain a basic glass melt.

[0009] S4. The boron-containing pre-reactant is added to the base glass melt in 2 to 4 portions, with a time interval of 5 to 15 minutes between two adjacent additions. During the addition process, the melting temperature is maintained at 1400℃ to 1500℃. After all the boron-containing pre-reactant has been added, the melt is melted at 1520℃ to 1580℃ for 60 to 150 minutes to obtain the shaped glass melt.

[0010] S5. The molten glass is shaped to obtain a glass container blank, and the glass container blank is annealed to obtain the heat-resistant, low-expansion glass container.

[0011] Further, based on the mass percentage of oxides, the molten glass comprises 75.0%–78.0% silicon dioxide, 10.5%–12.5% ​​boron trioxide, 3.5%–5.0% aluminum trioxide, 3.5%–4.8% sodium oxide, 0.8%–1.5% potassium oxide, 0.2%–0.6% lithium oxide, 0.6%–1.4% magnesium oxide, 0.2%–0.8% calcium oxide, and 0.1%–0.5% zirconium oxide, with the sum of the mass percentages of each component being 100%.

[0012] Further, the mass ratio of the sum of the lithium oxide and the potassium oxide to the mass of the sodium oxide is 0.25 to 0.50, the mass ratio of the boron trioxide to the sum of the masses of the lithium oxide, the sodium oxide, and the potassium oxide is 1.85 to 2.35, and the mass ratio of the aluminum trioxide to the sum of the masses of the lithium oxide and the potassium oxide is 2.0 to 3.5.

[0013] Further, in step S2, the temperature of the pre-reaction is 850℃~1050℃, and the time of the pre-reaction is 30min~90min; after the pre-reaction is completed, the pre-reaction product is cooled and crushed to obtain the boron-containing pre-reaction material with a particle size of 0.5mm~3.0mm.

[0014] Further, the method for detecting the water-soluble boron ratio includes: weighing 10.00g of the boron-containing pre-reaction material, adding 100mL of deionized water at 25℃, stirring at 300r / min for 30min, filtering, determining the boron content in the filtrate using inductively coupled plasma atomic emission spectrometry, and converting the boron content into the mass of water-soluble boron trioxide; separately weighing 10.00g of the same batch of the boron-containing pre-reaction material, after alkali fusion and acid dissolution treatment, determining the total boron content using inductively coupled plasma atomic emission spectrometry, and converting the total boron content into the total mass of boron trioxide; the water-soluble boron ratio is the percentage of the mass of water-soluble boron trioxide to the total mass of boron trioxide.

[0015] Furthermore, in step S4, the mass of the boron-containing pre-reactant added each time accounts for 15% to 50% of the total mass of the boron-containing pre-reactant, and the base glass melt is stirred and homogenized after each addition of the boron-containing pre-reactant.

[0016] Furthermore, the first boron source is borax, the second boron source is boric acid, and the sodium oxide introduced by the borax is included in the total sodium source.

[0017] Further, in step S5, the forming temperature is 1150℃~1250℃; the annealing includes holding the glass container preform at a temperature 10℃~25℃ higher than the glass transition temperature for 20min~50min, cooling it at a cooling rate of 0.5℃ / min~1.5℃ / min to a temperature 40℃~60℃ lower than the glass transition temperature, and then cooling it at a cooling rate of 2℃ / min~5℃ / min to below 300℃.

[0018] The present invention also provides a heat-resistant, low-expansion glass container, comprising, by mass percentage of oxides, 75.0%–78.0% silicon dioxide, 10.5%–12.5% ​​boron trioxide, 3.5%–5.0% aluminum trioxide, 3.5%–4.8% sodium oxide, 0.8%–1.5% potassium oxide, 0.2%–0.6% lithium oxide, 0.6%–1.4% magnesium oxide, 0.2%–0.8% calcium oxide, and 0.1%–0.5% zirconium oxide, wherein the sum of the mass percentages of each component is 100%.

[0019] Further, the mass ratio of the sum of the lithium oxide and the potassium oxide to the mass of the sodium oxide is 0.25 to 0.50, the mass ratio of the boron trioxide to the sum of the masses of the lithium oxide, the sodium oxide, and the potassium oxide is 1.85 to 2.35, and the mass ratio of the aluminum trioxide to the sum of the masses of the lithium oxide and the potassium oxide is 2.0 to 3.5.

[0020] This invention provides a heat-resistant, low-expansion glass container and its preparation method. It has the following beneficial effects:

[0021] 1. This invention divides the boron source into a first boron source and a second boron source. The second boron source, all lithium sources, 50% to 80% of the total potassium source, 20% to 40% of the total aluminum source, and 5% to 12% of the total silicon source are pre-reacted without the addition of a sodium source. After the formation of the base glass melt, a boron-containing pre-reactant is added. This reduces the volatilization of the boron source during the high-temperature melting process, improves the retention rate of boron trioxide content, and makes the actual boron trioxide content close to the design content.

[0022] 2. The present invention controls the proportion of water-soluble boron in the boron-containing pre-reactant to be 8% to 18%, which can avoid the increase of boron source volatilization caused by an excessively high proportion of water-soluble boron, and at the same time avoid the difficulty in fully dissolving and homogenizing the boron-containing pre-reactant in the base glass melt due to an excessively low proportion of water-soluble boron. Thus, while improving the retention rate of boron trioxide content, it ensures the homogenization of the boron-containing pre-reactant in the base glass melt.

[0023] 3. In this invention, the boron-containing pre-reactant is added to the base glass melt in 2 to 4 batches, and the time interval between two adjacent additions and the melting temperature during the addition process are controlled so that the boron-containing pre-reactant gradually melts and homogenizes with the base glass melt, thereby reducing the difference in thermal expansion performance of different parts of the heat-resistant low-expansion glass container and improving the thermal shock resistance.

[0024] 4. By limiting the mass percentages of silicon dioxide, boron trioxide, aluminum trioxide, sodium oxide, potassium oxide, lithium oxide, magnesium oxide, calcium oxide, and zirconium oxide, and by limiting the mass ratio between alkali metal oxides and boron trioxide and aluminum trioxide, the present invention enables the molten glass to possess both melting and molding properties and low thermal expansion properties.

[0025] 5. The present invention determines the annealing and holding temperature and cooling process of the glass container blank based on the glass transition temperature, which can reduce the residual stress in the heat-resistant low-expansion glass container and improve the service stability of the heat-resistant low-expansion glass container. Attached Figure Description

[0026] Figure 1 A flowchart illustrating a method for preparing a heat-resistant, low-expansion glass container provided by the present invention;

[0027] Figure 2 A comparison chart showing the retention rate of boron trioxide content in the examples and comparative examples;

[0028] Figure 3 A comparison diagram of the average linear thermal expansion coefficients of different parts of the heat-resistant, low-expansion glass containers prepared in the examples and comparative examples.

[0029] Figure 4 A comparison diagram showing the range of average linear thermal expansion coefficients of the heat-resistant, low-expansion glass containers prepared in the examples and comparative examples.

[0030] Figure 5 This is a comparison chart showing the thermal shock temperature difference of the heat-resistant, low-expansion glass containers prepared in the examples and comparative examples. Detailed Implementation

[0031] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0032] During the melting process of borosilicate glass, the boron source is prone to volatilization under high-temperature conditions, causing the actual boron trioxide content in the molten glass to deviate from the designed content. This results in differences in the composition and thermal expansion properties of different parts of the heat-resistant, low-expansion glass container. Directly increasing the melting temperature or extending the melting time, while beneficial for raw material melting and homogenization, will further increase the volatilization loss of the boron source. If the boron source is completely pre-melted, it will increase the number of preparation steps and affect the efficiency of subsequent melting processes.

[0033] To address the aforementioned problems, this invention divides the boron source into a first boron source and a second boron source. The second boron source, all lithium sources, 50%–80% of the total potassium source, 20%–40% of the total aluminum source, and 5%–12% of the total silicon source are pre-reacted without the addition of a sodium source to obtain a boron-containing pre-reactant with a water-soluble boron content of 8%–18%. The first boron source, all sodium sources, the remaining potassium source, the remaining aluminum source, the remaining silicon source, as well as all magnesium sources, all calcium sources, and all zirconium sources are used to prepare a basic batching material, which is then melted to form a basic glass melt. Subsequently, the boron-containing pre-reactant material is added to the basic glass melt in stages, and after melting, a shaped glass melt is obtained. This shaped and annealed glass melt then yields a heat-resistant, low-expansion glass container. For example… Figure 1 As shown, the method for preparing a heat-resistant, low-expansion glass container provided by the present invention includes boron source identification, boron-containing pre-reaction material preparation, base glass liquid preparation, phased addition, melting and homogenization, forming, and annealing.

[0034] By controlling the raw material composition, water-soluble boron ratio, and timing of addition of the boron-containing pre-reactant, it is possible to reduce boron source volatilization while ensuring the pre-reactant is fully melted and homogenized in the base glass melt. This improves the boron trioxide content retention rate and enhances the uniformity of thermal expansion and thermal shock resistance of heat-resistant, low-expansion glass containers. This invention is based on the above research.

[0035] The main raw materials and reagents used in the following examples and comparative examples are as follows. Unless otherwise specified, all reagents are commercially available analytical grade or higher grade products.

[0036] The silicon source uses high-purity quartz sand, mainly composed of silicon dioxide (CAS number 14808-60-7), with a silicon dioxide purity of not less than 99.9%. The first boron source uses borax, specifically sodium tetraborate decahydrate (CAS number 1303-96-4), with a purity of not less than 99.5%. The second boron source uses boric acid (CAS number 10043-35-3), with a purity of not less than 99.5%. The aluminum source uses aluminum hydroxide (CAS number 21645-51-2), with a purity of not less than 99.0%. The sodium source uses anhydrous sodium carbonate (CAS number 497-19-8), with a purity of not less than 99.0%. The purity is below 99.5%; the potassium source is anhydrous potassium carbonate, CAS number 584-08-7, with a purity of not less than 99.0%; the lithium source is lithium carbonate, CAS number 554-13-2, with a purity of not less than 99.0%; the magnesium source is magnesium oxide, CAS number 1309-48-4, with a purity of not less than 99.0%; the calcium source is calcium carbonate, CAS number 471-34-1, with a purity of not less than 99.0%; the zirconium source is zirconium dioxide, CAS number 1314-23-4, with a purity of not less than 99.0%; the water used for the water-soluble boron ratio test is deionized water.

[0037] The sodium oxide introduced by borax is included in the total sodium source, and the actual amount of each raw material is calculated based on the purity of the raw material and the theoretical conversion rate of the corresponding oxide.

[0038] In the following examples, the total mass of oxides in the molten glass was 5,000 kg. The amounts of each raw material were calculated based on the pure substance mass, and the actual weighing was adjusted according to the purity of the raw materials. The amount of anhydrous sodium carbonate used has deducted the mass of sodium oxide introduced by borax; the sodium oxide introduced by borax is included in the total sodium source.

[0039] In each embodiment, the proportion of water-soluble boron was determined using the following method: 10.00 g of boron-containing pre-reaction material was weighed, 100 mL of deionized water at 25 °C was added, and the mixture was stirred at 300 r / min for 30 min and then filtered. The boron content in the filtrate was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES), and the boron content was converted to the mass of water-soluble boron trioxide. Separately, 10.00 g of the same batch of boron-containing pre-reaction material was weighed, and after alkali fusion and acid dissolution treatments, the total boron content was determined by ICP-AES, and the total boron content was converted to the total mass of boron trioxide. The proportion of water-soluble boron was the percentage of the mass of water-soluble boron trioxide to the total mass of boron trioxide.

[0040] In each embodiment, a differential scanning calorimeter was used to determine the glass transition temperature. The test atmosphere was nitrogen, and the heating rate was 10°C / min. The extrapolated starting temperature corresponding to the step change of the baseline in the differential scanning calorimeter curve was taken as the glass transition temperature.

[0041] The design composition of the molten glass in each embodiment is shown in Table 1.

[0042] Table 1. Design composition of the molten glass in each embodiment.

[0043] silicon dioxide 76.10% 75.00% 77.70% 77.70% 76.25% Boron trioxide 11.80% 12.50% 10.80% 11.10% 12.30% Aluminum oxide 4.20% 5.00% 3.50% 3.50% 3.50% Sodium oxide 4.00% 4.00% 4.30% 4.80% 3.50% potassium oxide 1.20% 1.20% 1.00% 0.90% 1.25% Lithium oxide 0.40% 0.30% 0.30% 0.30% 0.50% magnesium oxide 1.00% 1.30% 1.20% 1.00% 1.40% Calcium oxide 0.80% 0.40% 0.70% 0.50% 0.80% Zirconia 0.50% 0.30% 0.50% 0.20% 0.50% total 100.00% 100.00% 100.00% 100.00% 100.00%

[0044] The oxide mass ratios corresponding to the design composition of the molten glass in each embodiment are shown in Table 2.

[0045] Table 2. Oxide mass ratios corresponding to the design composition of the molten glass in each embodiment.

[0046] The ratio of the sum of the masses of lithium oxide and potassium oxide to the mass of sodium oxide 0.400 0.375 0.302 0.250 0.500 The ratio of the mass of boron trioxide to the sum of the masses of lithium oxide, sodium oxide, and potassium oxide. 2.107 2.273 1.929 1.850 2.343 The ratio of the mass of aluminum oxide to the sum of the masses of lithium oxide and potassium oxide 2.625 3.333 2.692 2.917 2.000

[0047] Example 1

[0048] This embodiment provides a method for preparing a heat-resistant, low-expansion glass container, including the following steps:

[0049] S1. Based on the designed quality of boron trioxide in the molten glass, the boron source is divided into the first boron source and the second boron source.

[0050] The designed mass of boron trioxide in the molten glass is 590.00 g. The mass of boron trioxide corresponding to the first boron source is 236.00 g, accounting for 40% of the designed mass of boron trioxide; the mass of boron trioxide corresponding to the second boron source is 354.00 g, accounting for 60% of the designed mass of boron trioxide.

[0051] The first boron source uses borax, and the second boron source uses boric acid.

[0052] S2. Weigh out 628.79g boric acid, 49.46g lithium carbonate, 61.62g anhydrous potassium carbonate, 96.39g aluminum hydroxide and 304.40g high-purity quartz sand.

[0053] Of these, 61.62g of anhydrous potassium carbonate accounts for 70% of the total potassium source, 96.39g of aluminum hydroxide accounts for 30% of the total aluminum source, 304.40g of high-purity quartz sand accounts for 8% of the total silicon source, and 49.46g of lithium carbonate is the entire lithium source.

[0054] The above raw materials were mixed for 20 minutes, and then heated to 950°C at a rate of 10°C / min without the addition of a sodium source. The mixture was pre-reacted at 950°C for 60 minutes to obtain a pre-reaction product. The pre-reaction product was cooled to room temperature, crushed, and sieved to obtain a boron-containing pre-reaction material with a particle size of 1.0 mm to 2.0 mm.

[0055] The water-soluble boron content of the boron-containing pre-reaction material was determined to be 13% according to the aforementioned method for detecting the proportion of water-soluble boron.

[0056] S3. Weigh out 646.40g borax, 162.37g anhydrous sodium carbonate, 26.41g anhydrous potassium carbonate, 224.92g aluminum hydroxide, 3500.60g high-purity quartz sand, 50.00g magnesium oxide, 71.39g calcium carbonate and 25.00g zirconium dioxide.

[0057] Of these, 26.41g of anhydrous potassium carbonate is the remaining potassium source, 224.92g of aluminum hydroxide is the remaining aluminum source, 3500.60g of high-purity quartz sand is the remaining silicon source, 646.40g of borax is the first boron source, and 162.37g of anhydrous sodium carbonate, together with the sodium oxide introduced by borax, constitutes the entire sodium source.

[0058] The above raw materials are mixed for 20 minutes to obtain the basic batch. The basic batch is then put into a glass melting furnace and melted at 1420°C for 60 minutes to obtain the basic glass melt.

[0059] S4. Add the boron-containing pre-reactant to the base glass melt in three portions. The mass of each portion is 33%, 33%, and 34% of the total mass of the boron-containing pre-reactant, respectively. The time interval between two adjacent additions is 10 minutes, calculated from the time the previous addition is completed.

[0060] During the addition process, the melting temperature is maintained at 1450℃. After each addition of the boron-containing pre-reactant, stir at 20 rpm for 5 minutes. After all the boron-containing pre-reactant has been added, the temperature is raised to 1550℃ and melted for 105 minutes to obtain the shaped glass melt.

[0061] S5. Cool the molten glass to 1200℃ and use the pressure blow molding method to obtain the glass container blank.

[0062] The glass transition temperature of the glass container preform was determined. The glass container preform was kept at a temperature 18°C ​​above the glass transition temperature for 35 minutes, cooled at a cooling rate of 1.0°C / min to a temperature 50°C below the glass transition temperature, and then cooled at a cooling rate of 3.5°C / min to below 300°C. Subsequently, it was allowed to cool naturally to room temperature to obtain a heat-resistant, low-expansion glass container.

[0063] Example 2

[0064] This embodiment provides a method for preparing a heat-resistant, low-expansion glass container, including the following steps:

[0065] S1. The designed mass of boron trioxide in the molten glass is 625.00 g. The mass of boron trioxide corresponding to the first boron source is 187.50 g, accounting for 30% of the designed mass of boron trioxide; the mass of boron trioxide corresponding to the second boron source is 437.50 g, accounting for 70% of the designed mass of boron trioxide.

[0066] The first boron source uses borax, and the second boron source uses boric acid.

[0067] S2. Weigh out 777.10g boric acid, 37.09g lithium carbonate, 44.02g anhydrous potassium carbonate, 76.50g aluminum hydroxide and 187.50g high-purity quartz sand.

[0068] Of these, 44.02g of anhydrous potassium carbonate accounts for 50% of the total potassium source, 76.50g of aluminum hydroxide accounts for 20% of the total aluminum source, 187.50g of high-purity quartz sand accounts for 5% of the total silicon source, and 37.09g of lithium carbonate is the entire lithium source.

[0069] The above raw materials were mixed for 20 minutes, and then heated to 850°C at a rate of 10°C / min without the addition of a sodium source. The mixture was pre-reacted at 850°C for 90 minutes to obtain a pre-reaction product. The pre-reaction product was cooled to room temperature, crushed, and sieved to obtain a boron-containing pre-reaction material with a particle size of 0.5 mm to 1.5 mm.

[0070] The water-soluble boron ratio was tested according to the aforementioned method, and the water-soluble boron ratio of the boron-containing pre-reaction material was 18%.

[0071] S3. Weigh out 513.56g borax, 199.29g anhydrous sodium carbonate, 44.02g anhydrous potassium carbonate, 306.01g aluminum hydroxide, 3562.50g high-purity quartz sand, 65.00g magnesium oxide, 35.70g calcium carbonate and 15.00g zirconium dioxide.

[0072] The above raw materials are mixed for 20 minutes to obtain the basic batch. The basic batch is then put into a glass melting furnace and melted at 1380°C for 90 minutes to obtain the basic glass melt.

[0073] S4. Add the boron-containing pre-reactant to the base glass melt in two portions, each portion accounting for 50% of the total mass of the boron-containing pre-reactant, with a time interval of 15 minutes between the two additions.

[0074] During the addition process, the melting temperature is maintained at 1400℃. After each addition of the boron-containing pre-reactant, stir at 20 rpm for 5 minutes. After all the boron-containing pre-reactant has been added, the temperature is raised to 1520℃ and melted for 150 minutes to obtain the shaped glass melt.

[0075] S5. Cool the molten glass to 1150℃ and form it using the pressure blow molding method to obtain a glass container blank.

[0076] The glass container preform is held at a temperature 10°C above the glass transition temperature for 50 minutes, then cooled at a rate of 0.5°C / min to a temperature 40°C below the glass transition temperature, and then cooled at a rate of 2.0°C / min to below 300°C. Finally, it is allowed to cool naturally to room temperature to obtain a heat-resistant, low-expansion glass container.

[0077] Example 3

[0078] This embodiment provides a method for preparing a heat-resistant, low-expansion glass container, including the following steps:

[0079] S1. The designed mass of boron trioxide in the molten glass is 540.00 g. The mass of boron trioxide corresponding to the first boron source is 270.00 g, accounting for 50% of the designed mass of boron trioxide; the mass of boron trioxide corresponding to the second boron source is 270.00 g, accounting for 50% of the designed mass of boron trioxide.

[0080] The first boron source uses borax, and the second boron source uses boric acid.

[0081] S2. Weigh out 479.58g boric acid, 37.09g lithium carbonate, 58.69g anhydrous potassium carbonate, 107.10g aluminum hydroxide and 466.20g high-purity quartz sand.

[0082] Of these, 58.69g of anhydrous potassium carbonate accounts for 80% of the total potassium source, 107.10g of aluminum hydroxide accounts for 40% of the total aluminum source, 466.20g of high-purity quartz sand accounts for 12% of the total silicon source, and 37.09g of lithium carbonate is the entire lithium source.

[0083] The above raw materials were mixed for 20 minutes, and then heated to 1050°C at a rate of 10°C / min without the addition of a sodium source. The mixture was pre-reacted at 1050°C for 30 minutes to obtain a pre-reaction product. The pre-reaction product was cooled to room temperature, crushed, and sieved to obtain a boron-containing pre-reaction material with a particle size of 2.0 mm to 3.0 mm.

[0084] The water-soluble boron content of the boron-containing pre-reaction material was tested according to the aforementioned method, and the water-soluble boron content was 8%.

[0085] S3. Weigh out 739.52g borax, 162.14g anhydrous sodium carbonate, 14.67g anhydrous potassium carbonate, 160.66g aluminum hydroxide, 3418.80g high-purity quartz sand, 60.00g magnesium oxide, 62.47g calcium carbonate and 25.00g zirconium dioxide.

[0086] The above raw materials are mixed for 20 minutes to obtain the basic batch. The basic batch is then put into a glass melting furnace and melted at 1450°C for 30 minutes to obtain the basic glass melt.

[0087] S4. Add the boron-containing pre-reactant to the base glass melt in 4 portions, with each addition accounting for 25% of the total mass of the boron-containing pre-reactant, and the time interval between two adjacent additions is 5 minutes.

[0088] During the addition process, the melting temperature is maintained at 1500℃. After each addition of the boron-containing pre-reactant, stir at 20 rpm for 5 minutes. After all the boron-containing pre-reactant has been added, the temperature is raised to 1580℃ and melted for 60 minutes to obtain the shaped glass melt.

[0089] S5. Cool the molten glass to 1250℃ and form it using the pressure blow molding method to obtain a glass container blank.

[0090] The glass container preform is held at a temperature 25°C above the glass transition temperature for 20 minutes, then cooled at a rate of 1.5°C / min to a temperature 60°C below the glass transition temperature, and then cooled at a rate of 5.0°C / min to below 300°C. Finally, it is allowed to cool naturally to room temperature to obtain a heat-resistant, low-expansion glass container.

[0091] Example 4

[0092] This embodiment provides a method for preparing a heat-resistant, low-expansion glass container, including the following steps:

[0093] S1. The designed mass of boron trioxide in the molten glass is 555.00 g. The mass of boron trioxide corresponding to the first boron source is 249.75 g, accounting for 45% of the designed mass of boron trioxide; the mass of boron trioxide corresponding to the second boron source is 305.25 g, accounting for 55% of the designed mass of boron trioxide.

[0094] The first boron source uses borax, and the second boron source uses boric acid.

[0095] S2. Weigh out 542.20g boric acid, 37.09g lithium carbonate, 39.61g anhydrous potassium carbonate, 66.94g aluminum hydroxide and 271.95g high-purity quartz sand.

[0096] Of these, 39.61g of anhydrous potassium carbonate accounts for 60% of the total potassium source, 66.94g of aluminum hydroxide accounts for 25% of the total aluminum source, 271.95g of high-purity quartz sand accounts for 7% of the total silicon source, and 37.09g of lithium carbonate is the entire lithium source.

[0097] The above raw materials were mixed for 20 minutes, and then heated to 900°C at a rate of 10°C / min without the addition of a sodium source. The mixture was pre-reacted at 900°C for 75 minutes to obtain a pre-reaction product. The pre-reaction product was cooled to room temperature, crushed, and sieved to obtain a boron-containing pre-reaction material with a particle size of 1.0 mm to 2.5 mm.

[0098] The water-soluble boron ratio was tested according to the aforementioned method, and the water-soluble boron ratio of the boron-containing pre-reaction material was 15%.

[0099] S3. Weigh out 684.06g borax, 220.31g anhydrous sodium carbonate, 26.41g anhydrous potassium carbonate, 200.82g aluminum hydroxide, 3613.05g high-purity quartz sand, 50.00g magnesium oxide, 44.62g calcium carbonate and 10.00g zirconium dioxide.

[0100] The above raw materials are mixed for 20 minutes to obtain the basic batch. The basic batch is then put into a glass melting furnace and melted at 1400°C for 75 minutes to obtain the basic glass melt.

[0101] S4. Add the boron-containing pre-reactant to the base glass melt in three portions, with the mass of each portion accounting for 30%, 30%, and 40% of the total mass of the boron-containing pre-reactant, respectively, and the time interval between two adjacent additions being 12 minutes.

[0102] During the addition process, the melting temperature is maintained at 1430℃. After each addition of the boron-containing pre-reactant, stir at 20 rpm for 5 minutes. After all the boron-containing pre-reactant has been added, the temperature is raised to 1540℃ and melted for 120 minutes to obtain the molten glass.

[0103] S5. Cool the molten glass to 1180℃ and form it using the pressure blow molding method to obtain a glass container blank.

[0104] The glass container preform is held at a temperature 15°C above the glass transition temperature for 40 minutes, then cooled at a rate of 0.8°C / min to a temperature 45°C below the glass transition temperature, and then cooled at a rate of 3.0°C / min to below 300°C. Finally, it is allowed to cool naturally to room temperature to obtain a heat-resistant, low-expansion glass container.

[0105] Example 5

[0106] This embodiment provides a method for preparing a heat-resistant, low-expansion glass container, including the following steps:

[0107] S1. The designed mass of boron trioxide in the molten glass is 615.00 g. The mass of boron trioxide corresponding to the first boron source is 215.25 g, accounting for 35% of the designed mass of boron trioxide; the mass of boron trioxide corresponding to the second boron source is 399.75 g, accounting for 65% of the designed mass of boron trioxide.

[0108] The first boron source uses borax, and the second boron source uses boric acid.

[0109] S2. Weigh out 710.05g boric acid, 61.82g lithium carbonate, 68.78g anhydrous potassium carbonate, 93.72g aluminum hydroxide and 381.25g high-purity quartz sand.

[0110] Of these, 68.78g of anhydrous potassium carbonate accounts for 75% of the total potassium source, 93.72g of aluminum hydroxide accounts for 35% of the total aluminum source, 381.25g of high-purity quartz sand accounts for 10% of the total silicon source, and 61.82g of lithium carbonate is the entire lithium source.

[0111] The above raw materials were mixed for 20 minutes, and then heated to 1000°C at a rate of 10°C / min without the addition of a sodium source. The mixture was pre-reacted at 1000°C for 45 minutes to obtain a pre-reaction product. The pre-reaction product was cooled to room temperature, crushed, and sieved to obtain a boron-containing pre-reaction material with a particle size of 1.5 mm to 2.5 mm.

[0112] The water-soluble boron ratio was tested according to the aforementioned method, and the water-soluble boron ratio of the boron-containing pre-reaction material was 10%.

[0113] S3. Weigh out 589.57g borax, 135.41g anhydrous sodium carbonate, 22.93g anhydrous potassium carbonate, 174.05g aluminum hydroxide, 3431.25g high-purity quartz sand, 70.00g magnesium oxide, 71.39g calcium carbonate and 25.00g zirconium dioxide.

[0114] The above raw materials are mixed for 20 minutes to obtain the basic batch. The basic batch is then put into a glass melting furnace and melted at 1440°C for 45 minutes to obtain the basic glass melt.

[0115] S4. Add the boron-containing pre-reactant to the base glass melt in four portions. The mass of each addition is 15%, 25%, 30%, and 30% of the total mass of the boron-containing pre-reactant, respectively, with an 8-minute interval between each addition.

[0116] During the addition process, the melting temperature is maintained at 1480℃. After each addition of the boron-containing pre-reactant, stir at 20 rpm for 5 minutes. After all the boron-containing pre-reactant has been added, the temperature is raised to 1570℃ and melted for 75 minutes to obtain the molten glass.

[0117] S5. Cool the molten glass to 1230℃ and form it using the pressure blow molding method to obtain a glass container blank.

[0118] The glass container preform is held at a temperature 20°C above the glass transition temperature for 30 minutes, then cooled at a rate of 1.2°C / min to a temperature 55°C below the glass transition temperature, and then cooled at a rate of 4.0°C / min to below 300°C. Finally, it is allowed to cool naturally to room temperature to obtain a heat-resistant, low-expansion glass container.

[0119] Unless otherwise specified, the composition of the molten glass, the total theoretical mass of oxides, the types of raw materials, the amount of raw materials, the mixing time, the stirring conditions, the forming conditions, and the annealing conditions in the following comparative examples are the same as in Example 1. Each comparative example uses Example 1 as a control, and only one technical feature explicitly described is changed.

[0120] Comparative Example 1

[0121] The only difference between this comparative example and Example 1 is that a sodium source was added when preparing the boron-containing pre-reactant.

[0122] Specifically, in step S2 of Example 1, 162.37g of anhydrous sodium carbonate was mixed with 628.79g of boric acid, 49.46g of lithium carbonate, 61.62g of anhydrous potassium carbonate, 96.39g of aluminum hydroxide and 304.40g of high-purity quartz sand, and pre-reacted at 950°C for 60min. The mixture was then cooled, crushed and sieved to obtain a boron-containing pre-reaction material with a particle size of 1.0mm to 2.0mm.

[0123] In step S3, 162.37g of anhydrous sodium carbonate is no longer added. The other raw materials and their amounts in the basic batch are the same as in Example 1 to ensure that the designed quality of sodium oxide in the molten glass remains unchanged.

[0124] The remaining steps are the same as in Example 1, resulting in a heat-resistant, low-expansion glass container.

[0125] Comparative Example 2

[0126] The only difference between this comparative example and Example 1 is that the water-soluble boron content in the boron-containing pre-reactant is higher than 18%.

[0127] Specifically, in step S2 of Example 1, the type of raw material, amount of raw material, mixing time and pre-reaction temperature of the boron-containing pre-reaction material remain unchanged, and the pre-reaction time is adjusted from 60 min to 20 min to obtain the pre-reaction product.

[0128] The pre-reaction product was cooled to room temperature, crushed, and sieved to obtain a boron-containing pre-reaction material with a particle size of 1.0 mm to 2.0 mm. The water-soluble boron content was determined to be 24% using the aforementioned method for detecting the proportion of water-soluble boron.

[0129] The remaining steps are the same as in Example 1, resulting in a heat-resistant, low-expansion glass container.

[0130] Comparative Example 3

[0131] The only difference between this comparative example and Example 1 is that the water-soluble boron content in the boron-containing pre-reactant is less than 8%.

[0132] Specifically, in step S2 of Example 1, the type of raw material, amount of raw material, mixing time and pre-reaction temperature of the boron-containing pre-reaction material remain unchanged, and the pre-reaction time is adjusted from 60 min to 120 min to obtain the pre-reaction product.

[0133] The pre-reaction product was cooled to room temperature, crushed, and sieved to obtain a boron-containing pre-reaction material with a particle size of 1.0 mm to 2.0 mm. The water-soluble boron content of the pre-reaction material was determined to be 3% according to the aforementioned method for detecting the proportion of water-soluble boron.

[0134] The remaining steps are the same as in Example 1, resulting in a heat-resistant, low-expansion glass container.

[0135] Comparative Example 4

[0136] The only difference between this comparative example and Example 1 is that the boron-containing pre-reactant is added before the formation of the base glass melt.

[0137] Specifically, a boron-containing pre-reaction material with a water-soluble boron ratio of 13% and a particle size of 1.0 mm to 2.0 mm was prepared according to steps S1 and S2 of Example 1, and a basic batching material was prepared according to step S3 of Example 1.

[0138] The boron-containing pre-reacting material and the basic batching material are put into the glass melting furnace and melted at 1420℃ for 60 minutes. Then the melting temperature is adjusted to 1450℃ and held for 20 minutes, during which time it is stirred at 20 r / min for 15 minutes. Then the temperature is raised to 1550℃ and melted for 105 minutes to obtain the shaped glass liquid.

[0139] The raw material composition and amount of boron-containing pre-reacted material and basic batch are the same as in Example 1, except that the step of pre-melting the basic batch to form basic glass melt is omitted.

[0140] The subsequent molding and annealing steps are the same as in Example 1, resulting in a heat-resistant, low-expansion glass container.

[0141] Comparative Example 5

[0142] The only difference between this comparative example and Example 1 is that the boron-containing pre-reactant is added to the base glass melt in one step.

[0143] Specifically, boron-containing pre-reactant and base glass melt are prepared according to steps S1 to S3 of Example 1.

[0144] All boron-containing pre-reactant materials were added to the base glass melt at once. During the addition process, the melting temperature was maintained at 1450℃. The mixture was stirred at 20r / min for 15min after the addition was completed, and then kept at 1450℃ for 25min after the addition was completed. The temperature was then raised to 1550℃ and melted for 105min to obtain the shaped glass melt.

[0145] The total amount of boron-containing pre-reactant added, the total holding time at 1450°C after addition, and the total stirring time were the same as in Example 1, except that the addition was changed from three times to one time.

[0146] The subsequent molding and annealing steps are the same as in Example 1, resulting in a heat-resistant, low-expansion glass container.

[0147] Comparative Example 6

[0148] The only difference between this comparative example and Example 1 is that the mass of boron trioxide corresponding to the first boron source accounts for more than 50% of the designed mass of boron trioxide.

[0149] The designed mass of boron trioxide in the molten glass is 590.00 g. The mass of boron trioxide corresponding to the first boron source is 354.00 g, accounting for 60% of the designed mass of boron trioxide; the mass of boron trioxide corresponding to the second boron source is 236.00 g, accounting for 40% of the designed mass of boron trioxide.

[0150] The first boron source was borax, and the second boron source was boric acid. The amount of the first boron source used was 969.60 g, and the amount of the second boron source used was 419.20 g.

[0151] The proportions of lithium, potassium, aluminum, and silicon sources in the boron-containing pre-reactant were the same as in Example 1. 72.55g of anhydrous sodium carbonate was used as the sodium source. The anhydrous sodium carbonate, together with the sodium oxide introduced from the first boron source, constituted the total sodium source, ensuring a designed mass of 200.00g of sodium oxide in the molten glass.

[0152] The pre-reaction conditions of the boron-containing pre-reactant, the melting conditions of the basic batch, the addition method of the boron-containing pre-reactant, the final melting conditions, the molding conditions, and the annealing conditions were all the same as in Example 1, resulting in a heat-resistant, low-expansion glass container.

[0153] Comparative Example 7

[0154] The only difference between this comparative example and Example 1 is that the mass of boron trioxide corresponding to the second boron source accounts for more than 70% of the designed mass of boron trioxide.

[0155] The designed mass of boron trioxide in the molten glass is 590.00 g. The mass of boron trioxide corresponding to the first boron source is 118.00 g, accounting for 20% of the designed mass of boron trioxide; the mass of boron trioxide corresponding to the second boron source is 472.00 g, accounting for 80% of the designed mass of boron trioxide.

[0156] The first boron source was borax, and the second boron source was boric acid. The amount of the first boron source used was 323.20 g, and the amount of the second boron source used was 838.39 g.

[0157] The proportions of lithium, potassium, aluminum, and silicon sources in the boron-containing pre-reactant were the same as in Example 1. 252.19 g of anhydrous sodium carbonate was used as the sodium source. The anhydrous sodium carbonate, together with the sodium oxide introduced from the first boron source, constituted the total sodium source, ensuring that the designed mass of sodium oxide in the molten glass was 200.00 g.

[0158] The pre-reaction conditions of the boron-containing pre-reactant, the melting conditions of the basic batch, the addition method of the boron-containing pre-reactant, the final melting conditions, the molding conditions, and the annealing conditions were all the same as in Example 1, resulting in a heat-resistant, low-expansion glass container.

[0159] Test Example: To verify the effects of the water-soluble boron ratio of the boron-containing pre-reactant, the location of the sodium source addition, the timing of the boron-containing pre-reactant addition, the number of times the boron-containing pre-reactant was added, and the distribution ratio of the first and second boron sources on the performance of heat-resistant, low-expansion glass containers, the following tests were conducted on the heat-resistant, low-expansion glass containers prepared in Examples 1-5 and Comparative Examples 1-7. All test results are taken as the average of three parallel batches.

[0160] Test Example 1: Maintenance of Water-Soluble Boron Ratio and Boron Trioxide Content

[0161] The proportion of water-soluble boron was determined according to the method described in the examples.

[0162] Samples were taken from the main body of the heat-resistant, low-expansion glass containers prepared in Examples 1-5 and Comparative Examples 1-7, respectively. The samples were crushed and mixed evenly. After alkali fusion and acid dissolution treatment, the boron content in the samples was determined by inductively coupled plasma atomic emission spectrometry, and the boron content was converted into the actual mass percentage of boron trioxide.

[0163] The boron trioxide content retention rate is the ratio of the actual mass percentage of boron trioxide to the designed mass percentage of boron trioxide. The test results are shown in Table 3. The comparison results of the boron trioxide content retention rates of the examples and comparative examples are as follows: Figure 2 As shown.

[0164] Table 3. Retention of water-soluble boron ratio and boron trioxide content

[0165] Example 1 13.0% 11.80% 11.56% 98.0% Example 2 18.0% 12.50% 12.20% 97.6% Example 3 8.0% 10.80% 10.53% 97.5% Example 4 15.0% 11.10% 10.84% 97.7% Example 5 10.0% 12.30% 12.00% 97.6% Comparative Example 1 13.2% 11.80% 11.17% 94.7% Comparative Example 2 24.0% 11.80% 11.08% 93.9% Comparative Example 3 3.0% 11.80% 11.59% 98.2% Comparative Example 4 13.0% 11.80% 11.23% 95.2% Comparative Example 5 13.0% 11.80% 11.38% 96.4% Comparative Example 6 13.1% 11.80% 11.27% 95.5% Comparative Example 7 12.9% 11.80% 11.47% 97.2%

[0166] As shown in Table 3, the proportion of water-soluble boron in the boron-containing pre-reaction materials in Examples 1 to 5 is 8% to 18%, and the boron trioxide content retention rate is not less than 97.5%.

[0167] Compared with Example 1, in Comparative Example 1, the retention rate of boron trioxide content decreased after adding a sodium source to the boron-containing pre-reactant; in Comparative Example 2, the retention rate of boron trioxide content further decreased when the water-soluble boron content of the boron-containing pre-reactant was 24%; and in Comparative Example 4, the retention rate of boron trioxide content decreased when the boron-containing pre-reactant was added before the formation of the base glass melt.

[0168] The water-soluble boron content of the boron-containing pre-reactant in Comparative Example 3 was 3%, and its boron trioxide content retention rate was relatively high, but it still needs to be evaluated in conjunction with the uniformity of the average linear thermal expansion coefficient and thermal shock resistance.

[0169] Test Example 2: Average Linear Thermal Expansion Coefficient and Its Uniformity

[0170] Samples were cut from the mouth, body and bottom of each group of heat-resistant low-expansion glass containers, and the samples were processed into test pieces with a length of 25 mm and a cross-section of 4 mm × 4 mm.

[0171] The thermal expansion meter was used for testing, with a test temperature range of 20℃ to 300℃ and a heating rate of 5℃ / min. Three samples were tested for each part, and the average value of the test results for each part was taken as the average linear thermal expansion coefficient of that part.

[0172] The difference between the maximum and minimum values ​​of the average linear thermal expansion coefficients at the container opening, container body, and container bottom is taken as the range of the average linear thermal expansion coefficients. The test results are shown in Table 4. The comparison results of the average linear thermal expansion coefficients of different parts of the heat-resistant, low-expansion glass containers prepared in the examples and comparative examples are shown below. Figure 3 As shown, the comparison results of the range of average linear thermal expansion coefficients are as follows: Figure 4 As shown.

[0173] Table 4. Test results of average linear thermal expansion coefficient

[0174] Unit: 10 -6 K -1

[0175] Group Average linear thermal expansion coefficient at the container opening Average linear thermal expansion coefficient of the container body Average linear thermal expansion coefficient at the bottom of the container Average linear thermal expansion coefficient range Example 1 3.40 3.43 3.48 0.08 Example 2 3.31 3.36 3.42 0.11 Example 3 3.64 3.70 3.76 0.12 Example 4 3.71 3.78 3.85 0.14 Example 5 3.26 3.31 3.36 0.10 Comparative Example 1 3.42 3.55 3.69 0.27 Comparative Example 2 3.43 3.60 3.74 0.31 Comparative Example 3 3.46 3.63 3.80 0.34 Comparative Example 4 3.44 3.58 3.73 0.29 Comparative Example 5 3.41 3.52 3.65 0.24 Comparative Example 6 3.43 3.59 3.69 0.26 Comparative Example 7 3.45 3.57 3.68 0.23

[0176] As shown in Table 4, the heat-resistant, low-expansion glass containers prepared in Examples 1-5 have a low average linear thermal expansion coefficient in the temperature range of 20℃ to 300℃, and the range of the average linear thermal expansion coefficients of the container mouth, the container body, and the container bottom is no greater than 0.14 × 10⁻⁶. -6 K -1 .

[0177] In Comparative Example 1, a sodium source was added to the boron-containing pre-reactant. In Comparative Examples 2 and 3, the proportion of water-soluble boron exceeded 8% to 18%. In Comparative Example 4, a boron-containing pre-reactant was added before the formation of the base glass melt. In Comparative Example 5, the boron-containing pre-reactant was added to the base glass melt all at once. All of these measures increased the range of the average linear thermal expansion coefficient.

[0178] Among them, although Comparative Example 3 has a high boron trioxide content retention rate, the proportion of water-soluble boron is too low, the homogenization degree of boron-containing pre-reactant in the base glass melt is reduced, and the difference in the average linear thermal expansion coefficient of different parts of the heat-resistant low-expansion glass container increases.

[0179] Test Example 3: Thermal Shock Resistance

[0180] For each test temperature difference, 20 samples were randomly selected from the heat-resistant low-expansion glass containers prepared in Examples 1-5 and Comparative Examples 1-7, and each sample was subjected to a thermal shock resistance test at only one test temperature difference.

[0181] Place the heat-resistant, low-expansion glass container in an electric thermostatic chamber and keep it at the set temperature for 30 minutes. Then, transfer it to water at a temperature of 18℃~22℃ within 10 seconds, keep it for 5 minutes, and then remove it to check whether the heat-resistant, low-expansion glass container has cracked.

[0182] The initial temperature difference for the test was 140℃, and then the temperature difference was increased step by step in increments of 10℃. The maximum temperature difference corresponding to at least 18 of the 20 heat-resistant low-expansion glass containers without breaking was taken as the heat shock temperature difference.

[0183] Table 5 Results of thermal shock resistance test

[0184] Example 1 200℃ Example 2 200℃ Example 3 180℃ Example 4 180℃ Example 5 210℃ Comparative Example 1 160℃ Comparative Example 2 150℃ Comparative Example 3 150℃ Comparative Example 4 160℃ Comparative Example 5 170℃ Comparative Example 6 160℃ Comparative Example 7 170℃

[0185] Depend on Figure 5 As shown in Table 5, the heat-resistant low-expansion glass containers prepared in Examples 1 to 5 have a thermal shock temperature difference of 180℃ to 210℃.

[0186] As shown in Tables 3 to 5, pre-reacting 50% to 80% of the total amount of the second boron source, all lithium sources, and potassium source, 20% to 40% of the total amount of aluminum source, and 5% to 12% of the total amount of silicon source without adding sodium source, so that the water-soluble boron ratio of the boron-containing pre-reactant is maintained at 8% to 18%, and the boron-containing pre-reactant is added to the base glass melt in 2 to 4 times after the base glass melt is formed, can improve the boron trioxide content retention rate, reduce the difference in the average linear thermal expansion coefficient of different parts of the heat-resistant low-expansion glass container, and improve the thermal shock resistance.

[0187] When the proportion of water-soluble boron is higher than 18%, the amount of unreacted boron components in the boron-containing pre-reactant increases, making boron loss more likely during melting. When the proportion of water-soluble boron is lower than 8%, the boron-containing pre-reactant is difficult to fully melt and homogenize in the base glass melt. A water-soluble boron proportion of 8% to 18% can improve the retention rate of boron trioxide content while ensuring the homogenization of the boron-containing pre-reactant in the base glass melt.

[0188] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a heat-resistant, low-expansion glass container, characterized in that, Includes the following steps: S1. According to the designed mass of boron trioxide in the molten glass, the boron source is divided into a first boron source and a second boron source. The boron trioxide mass corresponding to the first boron source accounts for 30% to 50% of the designed boron trioxide mass, and the boron trioxide mass corresponding to the second boron source accounts for 50% to 70% of the designed boron trioxide mass. The sum of the boron trioxide mass corresponding to the first boron source and the boron trioxide mass corresponding to the second boron source is the designed boron trioxide mass. S2. Mix the second boron source, all lithium sources, 50% to 80% of the total amount of potassium source, 20% to 40% of the total amount of aluminum source, and 5% to 12% of the total amount of silicon source, and carry out a pre-reaction without adding sodium source to obtain a boron-containing pre-reaction material with a water-soluble boron ratio of 8% to 18%. S3. Mix the first boron source, all sodium source, the remaining potassium source, the remaining aluminum source, the remaining silicon source, all magnesium source, all calcium source, and all zirconium source to obtain a basic batching material. Melt the basic batching material at 1380℃~1450℃ for 30min~90min to obtain a basic glass melt. S4. The boron-containing pre-reactant is added to the base glass melt in 2 to 4 portions, with a time interval of 5 to 15 minutes between two adjacent additions. During the addition process, the melting temperature is maintained at 1400℃ to 1500℃. After all the boron-containing pre-reactant has been added, the melt is melted at 1520℃ to 1580℃ for 60 to 150 minutes to obtain the shaped glass melt. S5. The molten glass is shaped to obtain a glass container blank, and the glass container blank is annealed to obtain the heat-resistant, low-expansion glass container.

2. The method for preparing a heat-resistant, low-expansion glass container according to claim 1, characterized in that, The molten glass, by mass percentage of oxides, comprises 75.0%–78.0% silicon dioxide, 10.5%–12.5% ​​boron trioxide, 3.5%–5.0% aluminum trioxide, 3.5%–4.8% sodium oxide, 0.8%–1.5% potassium oxide, 0.2%–0.6% lithium oxide, 0.6%–1.4% magnesium oxide, 0.2%–0.8% calcium oxide, and 0.1%–0.5% zirconium oxide, with the sum of the mass percentages of each component being 100%.

3. The method for preparing a heat-resistant, low-expansion glass container according to claim 2, characterized in that, The mass ratio of the sum of the lithium oxide and potassium oxide to the mass of sodium oxide is 0.25 to 0.50; the mass ratio of boron trioxide to the sum of the masses of lithium oxide, sodium oxide, and potassium oxide is 1.85 to 2.35; and the mass ratio of aluminum trioxide to the sum of the masses of lithium oxide and potassium oxide is 2.0 to 3.

5.

4. The method for preparing a heat-resistant, low-expansion glass container according to claim 1, characterized in that, In step S2, the temperature of the pre-reaction is 850℃~1050℃, and the time of the pre-reaction is 30min~90min; after the pre-reaction is completed, the pre-reaction product is cooled and crushed to obtain the boron-containing pre-reaction material with a particle size of 0.5mm~3.0mm.

5. The method for preparing a heat-resistant, low-expansion glass container according to claim 1, characterized in that, The method for detecting the water-soluble boron ratio includes: weighing 10.00g of the boron-containing pre-reaction material, adding 100mL of deionized water at 25℃, stirring at 300r / min for 30min, filtering, and determining the boron content in the filtrate using inductively coupled plasma atomic emission spectrometry (ICP-AES), and converting the boron content into the mass of water-soluble boron trioxide; separately weighing 10.00g of the same batch of the boron-containing pre-reaction material, after alkali fusion and acid dissolution treatment, determining the total boron content using ICP-AES, and converting the total boron content into the total mass of boron trioxide; the water-soluble boron ratio is the percentage of the mass of water-soluble boron trioxide to the total mass of boron trioxide.

6. The method for preparing a heat-resistant, low-expansion glass container according to claim 1, characterized in that, In step S4, the mass of the boron-containing pre-reactant added each time accounts for 15% to 50% of the total mass of the boron-containing pre-reactant. After each addition of the boron-containing pre-reactant, the base glass melt is stirred and homogenized.

7. The method for preparing a heat-resistant, low-expansion glass container according to claim 1, characterized in that, The first boron source is borax, the second boron source is boric acid, and the sodium oxide introduced by the borax is included in the total sodium source.

8. The method for preparing a heat-resistant, low-expansion glass container according to claim 1, characterized in that, In step S5, the forming temperature is 1150℃~1250℃; the annealing includes holding the glass container preform at a temperature 10℃~25℃ higher than the glass transition temperature for 20min~50min, cooling it at a cooling rate of 0.5℃ / min~1.5℃ / min to a temperature 40℃~60℃ lower than the glass transition temperature, and then cooling it at a cooling rate of 2℃ / min~5℃ / min to below 300℃.

9. A heat-resistant, low-expansion glass container, characterized in that, The oxides comprise 75.0%–78.0% silicon dioxide, 10.5%–12.5% ​​boron trioxide, 3.5%–5.0% aluminum trioxide, 3.5%–4.8% sodium oxide, 0.8%–1.5% potassium oxide, 0.2%–0.6% lithium oxide, 0.6%–1.4% magnesium oxide, 0.2%–0.8% calcium oxide, and 0.1%–0.5% zirconium oxide, with the sum of the mass percentages of all components being 100%.

10. The heat-resistant, low-expansion glass container according to claim 9, characterized in that, The mass ratio of the sum of the lithium oxide and potassium oxide to the mass of sodium oxide is 0.25 to 0.50; the mass ratio of boron trioxide to the sum of the masses of lithium oxide, sodium oxide, and potassium oxide is 1.85 to 2.35; and the mass ratio of aluminum trioxide to the sum of the masses of lithium oxide and potassium oxide is 2.0 to 3.5.